Reading football : how the popular press created an American spectacle - Oriard, Michael, 1948- (Cultural studies of the United States., 1993)
Is football an athletic contest or a social event? Is it a game of skill, a test of manhood, or merely an organized brawl? Michael Oriard asks these and other intriguing questions in Reading Football, the first contemporary book-length study of football's formative years. American football began in 1870s as a game to be played, not watched. Within a brief ten years, it had become a great public spectacle with an immense following. Not coincidentally, Oriard argues, football's formative years were also the golden age of print, an era when newspapers and periodicals reached a larger and more varied audience than ever before. These publications carried vast amounts of commentary about football conducted by journalists, coaches, ministers, college presidents and faculty, and various others. The daily newspaper in particular, Oriard argues, virtually created football as a popular spectacle.